Knowledge statements and belief statements: how do their differences matter for Science Education - ATHANASSIOS RAFTOPOULOS (Metaichmio Publications, 2015)
In this paper, I examine first the way knowledge-statements and belief-statements are questioned in ordinary language. The former are questioned by "how do you know?" questions, while the latter are questioned by "why do you believe?" questions. The answers to these questions are different. In the former case, one replies by providing the reasons that justify their being in position to know, whereas in the latter case, one replies by adducing the evidence for their statement. Then, I explore the epistemological repercussions of the difference in ordinary usage between the verbs 'to know' and 'to believe' and, drawing on these, I discuss the implication for science teaching.